STRATEGI PENGEMBANGAN USAHA KUE KERING PADA UMKM BERKAH KOTA PEKANBARU - Juliandini, Atika; Syahza, Almasdi; Indrawati, Henny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Micro, Small and Medium Enterprises (MSMEs) have an important role in the absorption of manpower, income distribution and improving people's welfare. One of MSMEs in Pekanbaru City is UMKM Berkah. In 2016 UMKM Berkah decreased the amount of production. This research aims to formulate an appropriate development strategy alternative to be applied to UMKM Berkah Pekanbaru City. The subject of the research is the pastry that sold in UMKM Berkah. Data analysis tools were performed using IFAS matrix analysis, EFAS matrix, SWOT matrix, IE matrix and SWOT quadrant. Based on the results of the research, it is known that the strength is the division of task is good enough, the availability of sufficient raw materials, packaging attractive products and have halal certificate and permit by public health office. The main disadvantage of this bussines is the market share is not yet widespread, while the chances are the habit of consumptive society, and the main threat is the product is easily imitated. There are seven alternative generated strategies, two S-O strategies, one S-T strategy, two W-O strategies and two W-T strategies. The main alternative strategy generated is the S-O strategy that is, by expanding the market to increase sales volume and develop inter-message facilities.Keywords: Development Strategy, SWOT Analysis, UMKM Berkah